PENGARUH KESULITAN KEUANGAN, KEPEMILIKAN INSTITUSIONAL, OPINI AUDIT DAN SPESIALISASI INDUSTRI AUDITOR TERHADAP AUDIT DELAY - Rusmala, Yanisa Intan; Atmini, Sari (Jurnal Riset Akuntansi Politala, 2024)
This study aims to investigate and obtain the empirical evidence of the effect of financial distress, institutional ownership, audit opinion, and auditor industry specialization on audit delay. This study applies quantitative approach, and involves secondary data of financial reports and audit reports accessed from the Indonesia Stock Exchange portal. The population includes 80 energy companies listed on the Indonesia Stock Exchange in 2020-2022, from which the samples of 21 companies are selected through purposive sampling, resulting in a total of 63 observable data. The results reveal the companies average audit delay of 99 days, which exceeds the reporting time limit. This study proves that audit opinion and auditor industry specialization show a negative effect on audit delay. However, this study does not prove the effect of financial distress and institutional ownership on audit delay.